1991
DOI: 10.1507/endocrj1954.38.195
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester-Induced LH Release in Pituitary Gonadotrophs: Effects of Antagonists of Calmodulin and GnRH.

Abstract: Abstract.The phorbol ester, 12-O-tetradecanoylphorbol-13-acetate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Early studies in gonadotrophs demonstrated that GnRH induces a change in localisation of CaM from the cytoplasm to the cell membrane and also indicated that it has a role in GnRH‐induced LH release, as well as in the expression of primary response genes, c‐ fos , c‐ jun and junB , . More recently, two of the better characterised signalling pathways downstream of CaM, the CaM‐dependent kinases (CaMKs) and the phosphatase, calcineurin, have been shown to play roles in transducing GnRH‐activated signals to gonadotrophin gene transcription and other aspects of gonadotroph function.…”
Section: Gonadotrophin‐releasing Hormone (Gnrh) the Gonadotroph And mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in gonadotrophs demonstrated that GnRH induces a change in localisation of CaM from the cytoplasm to the cell membrane and also indicated that it has a role in GnRH‐induced LH release, as well as in the expression of primary response genes, c‐ fos , c‐ jun and junB , . More recently, two of the better characterised signalling pathways downstream of CaM, the CaM‐dependent kinases (CaMKs) and the phosphatase, calcineurin, have been shown to play roles in transducing GnRH‐activated signals to gonadotrophin gene transcription and other aspects of gonadotroph function.…”
Section: Gonadotrophin‐releasing Hormone (Gnrh) the Gonadotroph And mentioning
confidence: 99%
“…CaMK, calmodulin-dependent kinase; CoR, receptor corepressor; ERK, extracellular-signal regulated kinase; HDAC, histone deacetylase; NFAT, nuclear factor of activated T-cells; PKA, protein kinase A; PKC, protein kinase C; PLC, phospholipase C; TORC, transducer of regulated CREB. c-fos, c-jun and junB, (22)(23)(24). More recently, two of the better characterised signalling pathways downstream of CaM, the CaMdependent kinases (CaMKs) and the phosphatase, calcineurin, have been shown to play roles in transducing GnRH-activated signals to gonadotrophin gene transcription and other aspects of gonadotroph function.…”
mentioning
confidence: 99%
“…We previously reported that protein kinase C and calmodulin-dependent kinase participate in GnRH-induced LH release, and that either kinase system has a regulatory effect on the other [1]. This finding suggested that both kinase systems are connected by metabolic pathway(s), which transmits regulatory signals in a bi-directional way.…”
mentioning
confidence: 97%